Atomic layer deposited TiO2 nanofilm on titanium implant for reduced the release of particles - Zhao, Xiangyu; Zhang, Xiaoxuan; Zhou, Zilan; Meng, Fanchun; Liu, Ruilin; Zhang, Mengyuan; Hao, Yujia; Xie, Qingpeng; Sun, Xiaojun; Zhang, Bin; Wang, Xing (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Titanium implants are widely used in surgeries for their biocompatibility and mechanical properties. However, excessive titanium particle release can cause implant failure. This study explores Atomic Layer Deposition (ALD) to coat commercially pure titanium (Cp-Ti) with TiO2, aiming to improve its frictional and corrosion resistance while reducing particle release. By comparing TiO2 films with varying ALD cycle numbers, we assess surface properties, particle release, friction, and corrosion performance, providing insights into mitigating particle release from implants. Methods: Cp-Ti surfaces were prepared and coated with TiO2 films of 100, 300, and 500 ALD cycles. Surface characterization involved SEM, EDX, and XRD. Friction was tested using SEM, nanoindentation, and ICP-MS. Corrosion resistance was evaluated through immersion tests and electrochemical analysis. Cytotoxicity was assessed using BMSCs. Results: Surface characterization revealed smoother surfaces with increased ALD cycles, confirming successful TiO2 deposition. Friction testing showed reduced friction coefficients with higher ALD cycles, supported by nanoindentation results. Corrosion resistance improved with increasing ALD cycles, as evidenced by electrochemical tests and reduced titanium release. Cytotoxicity studies showed no significant cytotoxic effects. Conclusion: ALD-coated TiO2 films significantly enhance frictional and corrosion resistance of titanium implants while reducing particle release. The study underscores the importance of ALD cycle numbers in optimizing film performance, offering insights for designing implants with improved properties.